2011
DOI: 10.1038/nrn2978
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell potential of glia: lessons from reactive gliosis

Abstract: Astrocyte-like cells, which act as stem cells in the adult brain, reside in a few restricted stem cell niches. However, following brain injury, glia outside these niches acquire or reactivate stem cell potential as part of reactive gliosis. Recent studies have begun to uncover the molecular pathways involved in this process. A comparison of molecular pathways activated after injury with those involved in the normal neural stem cell niches highlights strategies that could overcome the inhibition of neurogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
485
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 476 publications
(511 citation statements)
references
References 183 publications
19
485
0
7
Order By: Relevance
“…In this sense, and in addition to the well‐established increase in GFAP expression, we found that plaque‐associated reactive astrocytes selectively express BLBP, a typical marker for astrocyte‐like neuronal stem cells (Götz & Barde, 2005). This marker has been widely used for studying neuronal progenitors in embryonic and adult brains; however, the expression of BLPB is also a molecular signature for reactive astrocytes in many injury conditions (Robel, Berninger, & Gotz, 2011). We report here for the first time that the extracellular amyloid‐triggered astrogliosis in the brain of a transgenic Alzheimer's model can be monitored by the expression of BLBP.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, and in addition to the well‐established increase in GFAP expression, we found that plaque‐associated reactive astrocytes selectively express BLBP, a typical marker for astrocyte‐like neuronal stem cells (Götz & Barde, 2005). This marker has been widely used for studying neuronal progenitors in embryonic and adult brains; however, the expression of BLPB is also a molecular signature for reactive astrocytes in many injury conditions (Robel, Berninger, & Gotz, 2011). We report here for the first time that the extracellular amyloid‐triggered astrogliosis in the brain of a transgenic Alzheimer's model can be monitored by the expression of BLBP.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, some of this glial progeny derived from SEZ NSCs after injury becomes migratory toward the injury site (Benner et al, 2013), while local reactive astrocytes in the cerebral cortex GM do not migrate (Bardehle et al, 2013). NSC‐derived reactive astrocytes may exert beneficial functions in the injury site (Sabelström et al 2013), further emphasizing the significance of comparing the properties and molecular signature of endogenous adult NSCs with those of reactive astrocytes (for review, see Götz et al, 2015; Grégoire et al, 2015; Robel et al, 2011; Silver and Steindler, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A small number of candidates shared by reactive astrocytes and endogenous NSCs have already been identified and tested, including glial fibrillary acidic protein (GFAP), Nestin, Musashi, DSD1‐proteoglycan, and Tenascin‐C (for review, see Götz et al, 2015; Robel et al, 2011; Sirko et al, 2009). However, these proteins also appear in injury conditions without reactive proliferation of astrocytes and/or neurosphere formation (Kamphuis et al, 2012; Robel at al., 2011), thus emphasizing the need for additional molecular insights.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, parenchymal astrocytes in the neonatal brain may still have stem cell properties compared with the adult brain (59), suggesting that the neonatal brain has a higher capacity to heal itself after injury.…”
Section: Growth-promoting Environmentmentioning
confidence: 99%